2012
DOI: 10.3791/4377
|View full text |Cite
|
Sign up to set email alerts
|

Dissection, Culture, and Analysis of <em>Xenopus laevis</em> Embryonic Retinal Tissue

Abstract: The process by which the anterior region of the neural plate gives rise to the vertebrate retina continues to be a major focus of both clinical and basic research. In addition to the obvious medical relevance for understanding and treating retinal disease, the development of the vertebrate retina continues to serve as an important and elegant model system for understanding neuronal cell type determination and differentiation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . The neural retina consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…To determine xMD3 expression, total RNA from 40 optic vesicles [stage 25; without staining as described in McDonough et al (2012)] and 50 eyes (stage 42; removal of epidermis in rostro-caudal manner and eye isolation) was extracted following the manufacturer instructions (RNeasy mini kit, Qiagen) and a semi-quantitative PCR was performed for MD3 and GAPDH, with the following primers respectively: MD3 Fw, ACAATGAGAGATTCTGTTACAGACGGGG; MD3 Rv, AAGCTCCCAACAGTTACAGCATCCATGGCT; GAPDH Fw, ACTGCCACCCAGAAGAC; GAPDH Rv, AAGTGCTTATTCCTTAGATG.…”
Section: Methodsmentioning
confidence: 99%
“…To determine xMD3 expression, total RNA from 40 optic vesicles [stage 25; without staining as described in McDonough et al (2012)] and 50 eyes (stage 42; removal of epidermis in rostro-caudal manner and eye isolation) was extracted following the manufacturer instructions (RNeasy mini kit, Qiagen) and a semi-quantitative PCR was performed for MD3 and GAPDH, with the following primers respectively: MD3 Fw, ACAATGAGAGATTCTGTTACAGACGGGG; MD3 Rv, AAGCTCCCAACAGTTACAGCATCCATGGCT; GAPDH Fw, ACTGCCACCCAGAAGAC; GAPDH Rv, AAGTGCTTATTCCTTAGATG.…”
Section: Methodsmentioning
confidence: 99%
“…Each stage was collected in triplicates (n = 3) and each biological replicate was composed of pooled eye tissues from 20–30 animals/embryos. Eye ablation and tissue dissociation was performed in Liberase (Thermolysin Medium Research Grade, Roche, Indianapolis, IN) and/or calcium-magnesium free Modified Ringer solution (CMF-MR) (adapted from [ 81 ]). Dissociated tissues were immediately stored in TRIzol Reagent (Invitrogen, Carlsbad, CA) at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas xVIAAT was selected as a general inhibitory neural marker in whole-mount coexpression experiments, the specifically GABAergic probe xGAD67 was selected for cell culture experiments because previous studies have demonstrated that calcium spike frequency regulates xGAD67 expression in vitro (Watt et al, 2000 ). High-stringency FISH was performed on cell cultures using an anti-digoxigenin peroxidase antibody (Roche) and fluorescein–tyramide as the color substrate, following the protocol of Davidson and Keller ( 1999 ) with minor modifications as outlined by McDonough et al ( 2012 ). Sense probes were used to determine background level of fluorescence.…”
Section: Methodsmentioning
confidence: 99%